2009
DOI: 10.1083/jcb.200805147
|View full text |Cite
|
Sign up to set email alerts
|

Kank attenuates actin remodeling by preventing interaction between IRSp53 and Rac1

Abstract: In this study, insulin receptor substrate (IRS) p53 is identified as a binding partner for Kank, a kidney ankyrin repeat–containing protein that functions to suppress cell proliferation and regulate the actin cytoskeleton. Kank specifically inhibits the binding of IRSp53 with active Rac1 (Rac1G12V) but not Cdc42 (cdc42G12V) and thus inhibits the IRSp53-dependent development of lamellipodia without affecting the formation of filopodia. Knockdown (KD) of Kank by RNA interference results in increased lamellipodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…KANK1 mutations were also associated with myeloproliferative neoplasm, and a fusion protein of KANK1 with PDGFRB was found as an oncogene due to a t(5:9) translocation20. Although KANK1 alterations are frequently found in many solid tumors including MPNST, its detailed cellular and molecular mechanisms on tumorigenesis remain largely unknown, except, that it is able to regulate actin polymerization and cell migration through RAC1 and RHOA signaling2122.…”
mentioning
confidence: 99%
“…KANK1 mutations were also associated with myeloproliferative neoplasm, and a fusion protein of KANK1 with PDGFRB was found as an oncogene due to a t(5:9) translocation20. Although KANK1 alterations are frequently found in many solid tumors including MPNST, its detailed cellular and molecular mechanisms on tumorigenesis remain largely unknown, except, that it is able to regulate actin polymerization and cell migration through RAC1 and RHOA signaling2122.…”
mentioning
confidence: 99%
“…Liprin β-1 and -2 were identified as α-liprin binding proteins[5]. Here we present novel findings documenting increased abundance of liprin β-1 in melanoma and its strong association with Kank1 and Kank2 proteins which are involved in suppression of cellular proliferation and regulation of cell migration[6-8]. Interaction with Kank proteins implicates liprin β-1 in molecular events driving the tumor biology of melanoma.…”
Section: Introductionmentioning
confidence: 82%
“…As the most studied KANK family member, KANK1 was first identified as a growth suppressor in human kidney tumor cells (10). Studies suggested that the growth-inhibitory effect of KANK1 is mediated by regulating cytoskeletal actin organization to inhibit cell mobility (11)(12)(13). Consistently, deletion and down-regulation of the KANK1 gene have been found in many tumors (9, 14 -16) as well as neurological disorders (17,18).…”
Section: Kidney Ankyrin Repeat-containing Proteins (Kank1/2/3/4) Belomentioning
confidence: 98%